Kajian Paket Dosis Semi Organik terhadap Sifat Tanah dan Hasil Tanaman Padi (Oryza sativa L) - NARKA, I WAYAN; DIBIA, I NYOMAN; ATMAJA, I WAYAN DANA (Agrotrop : Journal on Agriculture Science; Vol 10 No 2 (2020), 2020)
The study of packages of semi-organic fertilization on soil properties, and yield of rice (Oryza sativa L) . The aim of this study was to know the effect of semi organic fertilization doses on soil properties and yield of rice. The Randomized block design (RBD), with 3 replications and 9 treatments was used in this study. P0 (without fertilizer), P1 (25 tons of organic fertilizer ha-1), P2 (300 kg of Urea ha-1, 150 kg SP36 ha-1 and 75 kg KCl ha-1), P3 (biourin liquid fertilizer) P4 (½ P1 + ½ P2), P5 (½ P1 + ½ P3, P6 (½ P2 + ½ P3), P7 (2/3P1 + 1/ 3 P2) and P8 (2/3P3 + 1/3P2). The results showed that the application of semi-organic fertilizer on soil properties such as soil salinity, C-organic content, P-available and Nitrogen content of soil significantly affected by the treatment, while potasium_available and soil pH is not significantly affected by the treatment.  Yield of rice had a very significant effected by treatment. The semi-organic fertilizer P4 (combination of 50 % anorganic + 50 % organic compost) and P6 (combination of 50 % inorganic + 50 % biourine) can produce oven dry grain 33.35 g per bushel and 32.63 g per bushel respectively or increased 57.91 % and 54.50 % of controls.